Investigation of hemotropic Mycoplasmas in fetuses and sows with reproductive failure - Bordin, Luiz Carlos; Gava, Danielle; Sonalio, Karina [UNESP]; Mechler-Dreibi, Marina Lopes [UNESP]; Zanella, Janice Reis Ciacci; Morés, Nelson; de Oliveira, Luís Guilherme [UNESP]; Vaz, Eliana Knackfuss (Elsevier, 2021)
Swine eperythrozoonosis or porcine hemoplasmosis is an infectious disease caused mainly by Mycoplasma suis and is distributed worldwide. This study investigated the occurrence of porcine hemothropic mycoplasmas (PHMs) in fetuses and sows with reproductive failure. Two hundred and seventy-six samples (80 sows’ blood and 196 fetal tissue samples) from 27 farms with reproductive disorders were evaluated. The PHMs DNA was detected in 15 out of 80 (18.7%) sows but it was not detected in the fetuses. The bacterial load ranged from 1.32 × 102 to 2.61 × 105 copies/µL. From the 27 tested herds, 11 (40.7%) showed at least one positive sow per farm. The majority of the reproductive problems observed in PMHs positive sows were stillborn fetuses (46.7%) and stillborn associated with fetal mummification (26.7%). So, we evidenced that porcine hemoplasmas circulate among sows in Brazilian herds, however, its real impact on reproductive problems remains unknown.
Keywords: Eperythrozoonosis; qPCR; Reproductive diseases; Swine